(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Art is a remarkable component of human civilization and culture. The work through which people’s sense of beauty, creative talents, imagination, intelligence and skills are expressed is called art. Art also has traditionally been created and developed in rural simple folk life. Such artifacts that are based on the rural folk life are called ‘folk art’. Bamboo and cane artifacts have special significance among the diverse folk art forms built and developed in the folk life of Assam. The folk life of Barpeta district as a part of the culture of Assam is no exception. In Barpeta, there have been celebrated many folk festivals such as Sonweri, Deul etc. with the belief of bamboo. Various folk artifacts related to traditional house-building, agriculture, fishing, weaving etc. are made of bamboo and cane. Moreover, various tools, masks, ‘japi’, musical instruments required for households are made from bamboo and cane. In terms of cooking and food the use of bamboo and cane is also remarkable. On the other hand, the current era is all about science and technology. In the context of innovations of science and technology, globalization in the world market and economic sector has threatened the existence of the contents of folk life. In view of the importance and significance of the artifacts made of bamboo and cane in the folk life of Assam as well as Barpeta and the challenges and changes brought about by globalization on contrary, our study presents a comprehensive study of the artifacts made of bamboo and cane in Barpeta district in the context of globalization. This study, which is based mainly on the data collected through field studies, deals with the subject in an analytical manner. This study can be expected to reveal much of the overall identity of the artifacts made of bamboo and cane in Assam as well as Barpeta district as well as its present and future status.